DDX3 participates in miRNA biogenesis and RNA interference through translational control of PACT and interaction with AGO2 - Ming‐Chih Lai; Yen‐Ling Yu; Chiao‐Nung Chen; Jau‐Song Yu; Hsin‐Yuan Hung; Shih‐Peng Chan (FEBS Open Bio)
DDX3 is a DEAD‐box RNA helicase that plays multiple roles in RNA metabolism, including translation. We previously reported that DDX3 is required for translation of PACT, a binding partner of Dicer, suggesting a role for DDX3 in microRNA (miRNA) biogenesis and RNA interference (RNAi). Emerging evidence suggests that DDX3 plays a vital role in tumorigenesis and cancer progression, however, its underlying mechanism is still not fully understood. Here, we showed that the control of PACT by DDX3 is conserved in human cells and Caenorhabditis elegans. Using a miRNA microarray, we found that DDX3 regulates the expression of a small subset of cancer‐related miRNAs. These oncogenic miRNAs were down‐regulated by knockdown of DDX3 or PACT and up‐regulated by overexpression of DDX3 or PACT in HEK293T cells. Similar results were obtained in human cancer HCT116 and HeLa cells. Dual luciferase reporter assay showed that DDX3 and PACT are required for short hairpin RNA (shRNA)‐induced RNAi. We also performed co‐immunoprecipitation to confirm the interaction between DDX3 and AGO2, a significant component of the RNA‐induced silencing complex, supporting a role for DDX3 in the RNAi pathway. We further examined the effects of DDX3 and PACT on cell proliferation, and stable overexpression of DDX3 in HEK293 cells results in loss of contact inhibition of cell growth. Hence, we propose that DDX3 may participate in cancer development by regulating the RNAi pathway.